2015
DOI: 10.1111/gtc.12312
|View full text |Cite
|
Sign up to set email alerts
|

Microphthalmia‐associated transcription factor is expressed in projection neurons of the mouse olfactory bulb

Abstract: Microphthalmia‐associated transcription factor (Mitf) is a key regulator for differentiation of the neural crest‐derived melanocytes. Mitf consists of multiple isoforms, including melanocyte‐specific Mitf‐M and widely expressed Mitf‐A and Mitf‐H. Mitf mRNAs are also expressed in the brain, although the identity of Mitf‐expressing cells remains unknown. We therefore aimed to identify Mitf‐expressing cells in the brain. By the immunohistochemical analysis, we detected Mitf‐expressing cells only in the olfactory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 53 publications
2
21
2
Order By: Relevance
“…Multiple MITF isoforms are known to be expressed from distinct promoters of the MITF gene, with different tissue expression profiles. Among those, the M‐isoform of MITF (MITF‐M) is expressed almost exclusively in melanocytes (Fuse, Yasumoto, Suzuki, Takahashi, & Shibahara, ), although it has also been detected in retinal pigment epithelium (Bharti, Liu, Csermely, Bertuzzi, & Arnheiter, ; Masuda & Esumi, ) and likely in mouse olfactory bulb projection neurons (mitral cells and tufted cells) (Ohba, Takeda, Yamamoto, & Shibahara, ). Besides CREB mentioned previously, multiple other transcription factors are involved in the regulation of MITF‐M at the transcriptional level, including paired box gene 3 (PAX3), SRY (sex‐determining region Y)‐box 10 (SOX10), lymphoid enhancer‐binding factor 1 (LEF1 or TCF), one cut domain 2 (ONECUT‐2), and MITF itself (reviewed in Kawakami & Fisher ).…”
Section: Central Determinants Of Melanocytic Pigmentationmentioning
confidence: 99%
“…Multiple MITF isoforms are known to be expressed from distinct promoters of the MITF gene, with different tissue expression profiles. Among those, the M‐isoform of MITF (MITF‐M) is expressed almost exclusively in melanocytes (Fuse, Yasumoto, Suzuki, Takahashi, & Shibahara, ), although it has also been detected in retinal pigment epithelium (Bharti, Liu, Csermely, Bertuzzi, & Arnheiter, ; Masuda & Esumi, ) and likely in mouse olfactory bulb projection neurons (mitral cells and tufted cells) (Ohba, Takeda, Yamamoto, & Shibahara, ). Besides CREB mentioned previously, multiple other transcription factors are involved in the regulation of MITF‐M at the transcriptional level, including paired box gene 3 (PAX3), SRY (sex‐determining region Y)‐box 10 (SOX10), lymphoid enhancer‐binding factor 1 (LEF1 or TCF), one cut domain 2 (ONECUT‐2), and MITF itself (reviewed in Kawakami & Fisher ).…”
Section: Central Determinants Of Melanocytic Pigmentationmentioning
confidence: 99%
“…The antibody thus obtained recognizes a common region that is shared by multiple MITF isoforms, including MITF-M and widely expressed MITF-A and MITF-H (Fuse et al 1999). Importantly, this antibody has been successfully used in immunohistochemical analysis (Ohba et al 2015. Dilutions of primary antibodies were 1:400 for anti-MITF and 1:100 for anti-GLI1 (BIOSS, Woburn, MA, USA).…”
Section: Immunohistochemical Analysis Of Human Hepatic Cancer Arraysmentioning
confidence: 99%
“…However, subsequent studies have suggested the pleiotropic functions of Mitf in various organs, including liver (Smith et al 1994), pancreas (Mazur et al 2013), kidney , lung (Takeda et al 2007), olfactory bulb (Ohba et al 2015), and frontal cortex (Takeda et al 2014;Ohba et al 2016). In particular, the Mitf vitiligo mouse, Mitf vit /Mitf vit , is characterized by retinal degeneration and the accumulation of retinyl palmitate in RPE and the liver (Smith et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The transcription factor MITF, best known as a master regulator of melanocytes [18], is specifically expressed in the M/T neurons of the OB [19]. As the M/T neurons are the key output neurons in the OB circuitry, Mitf might play a role in olfaction [19].…”
Section: Introductionmentioning
confidence: 99%
“…The transcription factor MITF, best known as a master regulator of melanocytes [18], is specifically expressed in the M/T neurons of the OB [19]. As the M/T neurons are the key output neurons in the OB circuitry, Mitf might play a role in olfaction [19]. Mitf is also expressed in a subset of tufted cells, the external tufted cells (ETC), which are excitatory and synapse with MC, but do not project out of the OB [20][21][22].…”
Section: Introductionmentioning
confidence: 99%